PENGARUH IMPLEMENTASI THE ANTI-BULLYING & TEASING PROGRAM FOR PRESCHOOL CLASSROOM TEMA KOMUNITAS OLEH GURU DALAM MENINGKATKAN PERILAKU PROSOSIAL ANAK USIA 4-5 TAHUN DI KELAS TAMAN KANAK-KANAK - , Yuliezar Perwira Dara, Prof. Dr. Amitya Kumara, MS., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Prosocial behavior of preschool children determines the success of social competence in interactions with peers. Prosocial behavior also contribute to children's ability in dealing with bullying behavior. The study aims to determine the effect the implementation of the anti-teasing and bullying programs for preschool classroom theme of community (an adaptation of Sprung, Froschl, & Hinitz, 2005) by teachers in improving prosocial behavior of preschool children. Subjects were a group of children (27 children) ages 4 to 5 years of kindergarten in Sleman regency, Yogyakarta, which expressed written consent to be involved and did not apply to other similar programs during the implementation of the program. Classroom teachers as tutors in the implementation of the program. Quasi experimental research was conducted, with experimental design interupted time series with removed treatment. The program was adapted from the manual The Anti-Bullying & Teasing program for Preschool Classroom (Sprung, Froschl, & Hinitz, 2005) consists of 10 classroom activities are carried out and measured every day successively in 30 minutes. Initial baseline was measured 4 times, the phase of program implementation is measured in 9 times of observation, and second baseline was measured 3 times. Data collected through observation by time sampling recording technique tally (pillar). Data was analyzed through repeated measures t-test and visual analysis within and between conditions, by observing the emergence of behavioral graphs and trend direction and level of behavioral change. The results showed that there were differences in the frequency of prosocial behavior when implementing the program than when it was not implemented. Child prosocial behavior increases when the program is applied and decreases when the program is stopped.